Answer:
Step-by-step explanation:
See a solution process below:
Step-by-step explanation:
Step 1) Solve the second equation for
x
:
2
x
−
2
y
=
18
2
x
−
2
y
+
2
y
=
18
+
2
y
2
x
−
0
=
18
+
2
y
2
x
=
18
+
2
y
2
x
2
=
18
+
2
y
2
2
x
2
=
18
2
+
2
y
2
x
=
9
+
y
Step 2) Substitute
(
9
+
y
)
for
x
in the first equation and solve for
y
:
4
x
+
3
y
=
−
13
becomes:
4
(
9
+
y
)
+
3
y
=
−
13
(
4
×
9
)
+
(
4
×
y
)
+
3
y
=
−
13
36
+
4
y
+
3
y
=
−
13
36
+
(
4
+
3
)
y
=
−
13
36
+
7
y
=
−
13
−
36
+
36
+
7
y
=
−
36
−
13
0
+
7
y
=
−
49
7
y
=
−
49
7
y
7
=
−
49
7
7
y
7
=
−
7
y
=
−
7
Step 3) Substitute
−
7
for
y
in the solution to the second equation at the end of Step 1 and calculate
x
:
x
=
9
+
y
becomes:
x
=
9
−
7
x
=
2
The solution is:
x
=
2
and
y
=
−
7
or
(
2
,
−
7
)
The solution is:
x
=
2
and
y
=
−
7
or
(
2
,
−
7
)